An appraisal of serum preptin levels in PCOS - Celik, Onder; Celik, Nilufer; Hascalik, Seyma; Sahin, Ibrahim; Aydin, Suleyman; Ozerol, Elif (Elsevier Science Inc, 2011)
Plasma preptin levels were higher in women with PCOS compared with the control group (mean +/- SD, 823.2 +/- 140.7 vs. 324.9 +/- 147.3 pg/mL). This article suggests a potential role of preptin in the pathogenesis of PCOS. (Fertil Steril (R) 2011; 95:314-6. (c) 2011 by American Society for Reproductive Medicine.)
Keywords: Preptin; insulin; PCOS